Beispiel Nr: 28
$ \text{Gegeben:} y=ax^2+bx+c \\ \text{Gesucht:} \\ \text{Scheitel und Scheitelform}\\ \text{Definitions- und Wertebereich} \\ \text{Nullstellen - Schnittpunkt mit der x-Achse} \\ \text{Faktorisiere Form} \\ \text{Scheitel} \\ Eigenschaften\\ \textbf{Gegeben:} \\ y=-\frac{1}{3}x^2-2x+3\\ \\ \textbf{Rechnung:} \\\bullet \text{Funktion} \\ y=-\frac{1}{3}x^2-2x+3\\ \\ \bullet \text{Scheitelberechnung } \\ \begin{array}{l|l|l} \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=-\frac{1}{3}x^2-2x+3 \\ y=-\frac{1}{3}(x^2+6x-9) \\ y=-\frac{1}{3}(x^2+6x+3^2-3^2-9) \\ y=-\frac{1}{3}[(x+3)^2-3^2-9] \\ y=-\frac{1}{3}[(x+3)^2-9-9] \\ y=-\frac{1}{3}[(x+3)^2-18] \\ y=-\frac{1}{3}(x+3)^2+6 \\ Scheitel(-3/6) \end{array} & \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=-\frac{1}{3}x^2-2x+3 \\ y=-\frac{1}{3}(x^2+6x)+3 \\ y=-\frac{1}{3}(x^2+6x+3^2-3^2)+3 \\ y=-\frac{1}{3}[(x+3)^2-3^2]+3 \\ y=-\frac{1}{3}[(x+3)^2-9]+3 \\ y=-\frac{1}{3}(x+3)^2+3+3 \\ y=-\frac{1}{3}(x+3)^2+6 \\ Scheitel(-3/6) \end{array} & \begin{array}{l} \text{Scheitelformel} \\ \hline y=-\frac{1}{3}x^2-2x+3 \\ xs=-\frac{-2}{2\cdot \left(-\frac{1}{3}\right)} \\ xs=-3 \\ ys=3-\frac{\left(-2\right)^2}{4\cdot\left(-\frac{1}{3}\right)} \\ ys=6 \\ Scheitel(-3/6)\\ y=-\frac{1}{3}(x+3)^2+6 \end{array} \\ \end{array} \\ \\ \\\bullet\text{Definitions- und Wertebereich:}\qquad \mathbb{D} = \mathbb{R} \qquad \mathbb{W} = ]-\infty;6]\\ \\=-\frac{1}{3}(x+7,24)(x-1,24)\\ \\\bullet \text{Nullstellen / Schnittpunkt mit der x-Achse:} \\y=-\frac{1}{3}x^2-2x+3 = 0 \\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ -\frac{1}{3}x^{2}-2x+3 =0 \\ x_{1/2}=\displaystyle\frac{+2 \pm\sqrt{\left(-2\right)^{2}-4\cdot \left(-\frac{1}{3}\right) \cdot 3}}{2\cdot\left(-\frac{1}{3}\right)} \\ x_{1/2}=\displaystyle \frac{+2 \pm\sqrt{8}}{-\frac{2}{3}} \\ x_{1/2}=\displaystyle \frac{2 \pm2,83}{-\frac{2}{3}} \\ x_{1}=\displaystyle \frac{2 +2,83}{-\frac{2}{3}} \qquad x_{2}=\displaystyle \frac{2 -2,83}{-\frac{2}{3}} \\ x_{1}=-7,24 \qquad x_{2}=1,24 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ -\frac{1}{3}x^{2}-2x+3 =0 \qquad /:-\frac{1}{3} \\ x^{2}+6x-9 =0 \\ x_{1/2}=\displaystyle -\frac{6}{2}\pm\sqrt{\left(\frac{6}{2}\right)^2- \left(-9\right)} \\ x_{1/2}=\displaystyle -3\pm\sqrt{18} \\ x_{1/2}=\displaystyle -3\pm4,24 \\ x_{1}=1,24 \qquad x_{2}=-7,24 \end{array}\\ \end{array}\\ \underline{x_1=-7,24; \quad1\text{-fache Nullstelle}} \\\underline{x_2=1,24; \quad1\text{-fache Nullstelle}} \\ \\ \bullet \text{Vorzeichentabelle:} \\ \begin{array}{|c|c|c|c|c|c|c||} \hline & x < &-7,24&< x <&1,24&< x\\ \hline f(x)&-&0&+&0&-\\ \hline \end{array}\\ \\ \underline{\quad x \in ]-7,24;1,24[\quad f(x)>0 \quad \text{oberhalb der x-Achse}}\\ \\ \underline{\quad x \in ]-\infty;-7,24[\quad \cup \quad]1,24;\infty[\quad f(x)<0 \quad \text{unterhalb der x-Achse}}$